Palliocystidium, a new genus in the family Hydnodontaceae (Trechisporales) - Alexander Ordynets; Gérald Gruhn (Plant Ecology and Evolution)
Background and aims – During fieldwork in French Guiana in 2018, two fungal specimens resembling Subulicystidium oberwinkleri were collected. This study aims to clarify species- and genus-level assignment of this material and of S. oberwinkleri. Material and methods – Corticioid fruiting bodies were examined under a light microscope, and spores from the spore prints were studied morphometrically. DNA sequences of large subunit-coding DNA and internal transcribed spacer were used for maximum likelihood and Bayesian phylogenetic analyses. Furthermore, guanine-cytosine content was calculated for the LSU dataset, and UNITE Species Hypotheses Matching Analysis was performed for newly generated ITS sequences. Key results – The new genus, Palliocystidium, is introduced in the family Hydnodontaceae, based on the peculiar pattern of cystidial encrustation (crystalline plates of various shapes) and cystidial septation and supported by results of phylogenetic analyses. Within the new genus, the new species P. chlamydatum from French Guiana is described. In addition, Subulicystidium oberwinkleri is transferred to Palliocystidium. The two species can be distinguished by the size of their reniform spores. Both species display high levels of guanine-cytosine content at the scale of the order Trechisporales. Conclusions – In the newly introduced genus Palliocystidium and genera Subulicystidium and Luellia, there is significant potential for further exploration of species diversity and generic boundaries. Additional intensified fruiting-body-based sampling of taxa and genes is necessary to clarify the relationship of genera within Hydnodontaceae.